Late Pleistocene lake level history of Lake Mungo, Australia. (15th June 2020) - Barrows, Timothy T.; Fitzsimmons, Kathryn E.; Mills, Stephanie C.; Tumney, Jacqui; Pappin, Daryl; Stern, Nicola
Abstract: Lake Mungo is a currently dry lake basin in the semi-arid zone of southeastern Australia. The transverse dune system on the downwind side contains a record of human occupation of international importance. It also contains one of the most continuous records of climate change over the last glacial cycle in the Australia desert. In this paper we provide a framework for the interpretation of lake level history from before the arrival of people (>41 ka) until after the establishment of the pastoral industry in the area. We present 83 optically stimulated luminescence ages from the Lake Mungo lunette. The lake level history is reconstructed from 34 stratigraphic sections along three transects through the lunette. The dating reveals considerable lake level fluctuations through time which occur over a depth range of ∼10 m in the basin. At its height, probably at multiple times before 20 ka, the lake held more than 1 km 3 of water and at its final level at ∼19 ka, contained only 0.03 km 3 . The inception of Lake Mungo appears to have taken place during the mid-Pleistocene between ∼256 and 369 ka. During the last glacial cycle, Lake Mungo was almost continuously wetter than present from shortly after 60 ka until ∼19 ka. The Upper Mungo, Arumpo and Zanci units represent a succession of lake filling and drying events, briefly interspersed by soils. The final Zanci unit does not represent a single high lake phase, but an initial lake filling followed by a series of short-lived lake level events within a brief period of a few thousand years. At the conclusion of this event, the lake remained dry until the present day. Four OSL ages from a linear dune upwind of Lake Mungo indicates regional aeolian activity from ∼30 ka until present. Widespread erosion that produces the characteristic topography of the lunette began after the arrival of British pastoralists and traditional aboriginal ways of life overlapped briefly with this erosion. The presence of water in Lake Mungo closely corresponds to periods when regional surface temperature was colder than present during the late Pleistocene. Our new data supports a model that decreased evaporation and increased runoff were primarily responsible for increased availability of surface water in the hydrological cycle. Highlights: The lake level history of Lake Mungo is reconstructed from 34 stratigraphic sections and 83 luminescence ages. The lake level fluctuated over a depth range of ∼10 m in the basin, from more than 1 km 3 of water to only 0.03 km 3 . The inception of the lake appears to have taken place during the mid-Pleistocene at ∼256–369 ka. The lake filled during the last glacial maximum. The presence of water in Lake Mungo corresponds to when regional surface temperature was significantly colder than present.